2020
DOI: 10.1155/2020/3801748
|View full text |Cite
|
Sign up to set email alerts
|

Four Autophagy-Related lncRNAs Predict the Prognosis of HCC through Coexpression and ceRNA Mechanism

Abstract: Abnormally expressed long noncoding RNAs (lncRNAs) have been reported to affect the occurrence and progression of hepatocellular carcinoma (HCC) by modulating the autophagy axis. However, none of studies has explored the clinical significance of these autophagy-related lncRNAs in HCC comprehensively. In this study, the RNA-seq, miRNA-seq, and clinical data of normal and HCC patients from the TCGA database and autophagy genes from the Human Autophagy Database were extracted. Subsequently, we screened out 78 dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 43 publications
2
32
0
Order By: Relevance
“…28 Meanwhile, lncRNA AC099850.3 was a member of the ARlncRNAs prognostic model and could serve as an indicator of hepatocellular carcinoma diagnosis and treatment. 29 The expression of SPINT1-AS1 was negatively correlated with esophageal squamous cell carcinoma (ESCC) patients' survival (p < 0.05), which suggested that they could act as tumor suppressors in ESCC. 30 Furthermore, lncRNA AC108449.2 could be used as a member of the ARlncRNAs prognostic model and the immune-related prognostic model for the diagnosis and treatment of bladder 31 and kidney carcinoma, 18 respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Meanwhile, lncRNA AC099850.3 was a member of the ARlncRNAs prognostic model and could serve as an indicator of hepatocellular carcinoma diagnosis and treatment. 29 The expression of SPINT1-AS1 was negatively correlated with esophageal squamous cell carcinoma (ESCC) patients' survival (p < 0.05), which suggested that they could act as tumor suppressors in ESCC. 30 Furthermore, lncRNA AC108449.2 could be used as a member of the ARlncRNAs prognostic model and the immune-related prognostic model for the diagnosis and treatment of bladder 31 and kidney carcinoma, 18 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNA AC099850.3 has been reported as a member of the lncRNA‐miRNA‐mRNA competitive endogenous RNA network that might be useful in the diagnosis and treatment of squamous cell carcinoma of the tongue 28 . Meanwhile, lncRNA AC099850.3 was a member of the ARlncRNAs prognostic model and could serve as an indicator of hepatocellular carcinoma diagnosis and treatment 29 . The expression of SPINT1‐AS1 was negatively correlated with esophageal squamous cell carcinoma (ESCC) patients’ survival ( p < 0.05), which suggested that they could act as tumor suppressors in ESCC 30 .…”
Section: Discussionmentioning
confidence: 99%
“…RP11-324I22.4 is an antisense lncRNA; the gene alias is lnc-CUL2-3. As cancer or tumor suppressor genes, antisense lncRNAs play an essential role in the occurrence and development of human cancer [55][56][57]. Although there is currently no disease research related to RP11-324I22.4, antisense lncRNAs may certainly be the promising tumor biomarker and therapeutic target in future research.…”
Section: Discussionmentioning
confidence: 99%
“…The examples we have cited are only the tip of the iceberg, and the relationship between lncRNA, ferroptosis, and LAUD has also been well demonstrated in this study from a new perspective. Among these lncRNAs of the signature, some studies have shown that AC099850.3 is also used as an autophagy-related lncRNA signature model in hepatocellular carcinoma as well as oral and oropharyngeal squamous cell carcinoma [46,47]. Benoist GE et al revealed that patients with NAALADL2-AS2 high-expression showed a longer time to progression [48].…”
Section: Discussionmentioning
confidence: 99%